Safety and immunogenicity of live attenuated influenza reassortant H5 vaccine (phase I–II clinical trials) - Rudenko, Larisa; Desheva, Julia; Korovkin, Sergey; Mironov, Alexander; Rekstin, Andrey; Grigorieva, Elena; Donina, Svetlana; Gambaryan, Alexandra; Katlinsky, Anton (Influenza and other respiratory viruses, 2008)
Objective  Our studies aimed to evaluate in clinical trials the safety and immunogenicity of an H5 live influenza vaccine candidate obtained using classical reassortment techniques from a low pathogenicity avian influenza (LPAI) A/Duck/Potsdam/1402‐6/86(H5N2) virus and the cold‐adapted (ca) donor strain A/Leningrad/134/17/57(H2N2). Methods  During Phase I–II clinical trials, volunteers received intranasally two doses of reassortant influenza vaccine strain A/17/Duck/Potsdam/86/92 (H5N2) 21 days apart. Clinical examination of all vaccinees was conducted 7 days post‐vaccination. Serum antibody responses were measured by hemagglutination‐inhibition and microneutralization and local antibodies were estimated using an enzyme‐linked immunosorbent assay test. Results  The vaccine was safe and of low reactogenicity with no febrile reactions. After revaccination 47·1–54·8% of subjects showed ≥fourfold seroconversions of Hamagglutination inhibition (HAI) antibodies to the hemagglutinin (HA) antigen of the A/17/Duck/Potsdam/86/92 (H5N2) virus and 29·4–30·8% were seroconverted to the HA antigen of the reverse genetics reassortant A/Indonesia/05/2005 × PR8 IBCDC‐RG (H5N1). Virus‐neutralizing antibody levels in sera of volunteers were similar to those shown in HAI test. The virus‐specific nasal IgA antibody response after two vaccine doses demonstrated significant increases of ≥fourfold rise SIgA antibodies (65%) geometrical mean titers (16·0) and a rise in SIgA antibodies (2·8) compared with one dose. Conclusion  The live attenuated influenza vaccine candidate prepared using the LPAI A(H5N2) strain was well tolerated and elicited serum and local immune responses. There was evident cross‐reactivity to the A(H5N1) strain in the HAI test.